GOOGLE SITES-BASED NUSANTARA STORYBOOKS INCREASE THE MOTIVATION TO STUDY IPAS FOR GRADE 3 ELEMENTARY SCHOOL STUDENTS - I Wayan Wira Kusumajaya; Komang Surya Adnyana; Putu Sanjaya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Learning is one-way lecture and student learning motivation is low. Therefore, learning improvements are implemented. The purpose of this study is to conduct classroom action research through the application of Google Sites-based Nusantara storybooks to increase student learning motivation. The implementation of the research is at SD N 3 Kekeran Bali with a research sample of 28 third-grade students. The classroom action research method with a pre-cycle, first cycle, and second cycle. The research instrument is a student learning motivation questionnaire. The results of the study showed an increase in the average student learning motivation from the first cycle with an average of 68 and classical completeness of 61% and the second cycle average to 85 and classical completeness to 93%. Therefore, it is concluded that the application of Google Sites-based Nusantara storybooks increases students' motivation to learn science, especially in the third grade of elementary school. Further research can develop media, insert models, or conduct experimental research with a wider sample.